Power Dynamics in the Arts Sponsorship : Activities in Bandung and Yogyakarta during COVID-19 - Aviandy, Mochamad; Fajarwati, Ade Ariyani Sari; Alkatiri, Zeffry; Yulianto, Kresno; Setiawan, Hawe (Bina Nusantara University, 2024)
The research objectively analyzed artists’ actions and strategic reactions in the urban areas of Bandung and Yogyakarta in Indonesia during the extremely turbulent COVID-19 pandemic from March 2020 to early 2021. The pandemic greatly impacted the lives of artists and practitioners because of stringent governmental prohibitions that prohibited public art events. The research examined practitioners’ experiences concerning their reliance or autonomy from government funding when engaging in arts-related endeavors. The research methodology was based on gathering data from social media and field investigations; a comprehensive collection of posters, photos, and relevant notes was compiled using a cultural studies framework. In addition, interviews were performed with arts practitioners and communities, specifically examining their involvement on social media platforms. A detailed investigation was conducted by carefully analyzing the interview data to clarify the differences between art practitioners in Bandung and Yogyakarta. It is found that the research distinguishes between individuals who receive government sponsorship and those who operate independently. It enhances the overall comprehension of power dynamics between arts practitioners and the government in the distinct setting of the COVID-19 epidemic, including those who operated autonomously. The research utilizes a cultural studies framework to examine the power dynamics between artists and the government in the context of the COVID-19 pandemic.